A modified surgical approach to a case of mandibular fracture in a 5-year-old girl - Attiguppe R Prabhakar; Kirthi Kumar Rai; Divya Prahlad (Wolters Kluwer Medknow Publications, 2013)
Injuries to the face are far more uncommon than other injuries in children. However, when they occur they can pose considerable management challenges to concerned specialists and the subsequent functional and esthetic impact to the growing child can be overwhelming. Here is a report of a 5-year-old girl diagnosed with fracture of the body of the mandible and an associated fracture of the parasymphysis. This paper presents a unique treatment modality considering the various anatomic and developmental factors in such young children.